Reforming mental disability law in Africa: practical tips and suggestions - Bartlett, Peter; Hamzic, Vanja (University of Nottingham, Human Rights Law Centre, 2010)
This report constitutes a major output of the project Designing Mental Health Law in Developing Countries: A Case Study of Lesotho which was directed by Professor Peter Bartlett, Nottinghamshire Healthcare NHS Trust Professor of Mental Health. The report provides examples of best practice, suggestions for future legislative reform initiatives and the direction of legislation and policy regarding service provision for people with mental disabilities.